Relative Performance Evaluation in CEO Compensation: A Talent-Retention Explanation - De Angelis, David; Grinstein, Yaniv (Journal of Financial and Quantitative Analysis, 2020)
Relative performance evaluation (RPE) in chief executive officer (CEO) compensation can be used as a commitment device to pay CEOs for their revealed relative talent. We find evidence consistent with the talent-retention hypothesis, using two different approaches. First, we examine the RPE terms in compensation contracts and document features that are consistent with retention motives. Second, using a novel empirical specification for detecting RPE, we find RPE is less prevalent when CEO talent is less transferrable: Among specialist CEOs, founder CEOs, and retirement-age CEOs, as well as in industries and states where the market for CEO talent is more restrictive.